2021
DOI: 10.3389/feart.2021.641760
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Element Incorporation in Calcium Carbonate Biominerals Recapitulate Phylogeny for a Diverse Range of Marine Calcifiers

Abstract: Elemental ratios in biogenic marine calcium carbonates are widely used in geobiology, environmental science, and paleoenvironmental reconstructions. It is generally accepted that the elemental abundance of biogenic marine carbonates reflects a combination of the abundance of that ion in seawater, the physical properties of seawater, the mineralogy of the biomineral, and the pathways and mechanisms of biomineralization. Here we report measurements of a suite of nine elemental ratios (Li/Ca, B/Ca, Na/Ca, Mg/Ca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 155 publications
(197 reference statements)
0
14
1
Order By: Relevance
“…We noted only a weak but significant positive correlation ( r 2 = 0.43-0.64, p-value < 0.001) for Mg/Mn, Cu/Mn, Zn/Mn and Sr/Mn, while Fe/Mn presented no significant correlation ( Supplementary Information 4 ). This difference in composition had already been observed and was probably due to vital effects (Weiner & Dove, 2003; Ulrich et al, 2021) induced by the metabolic filter between surrounding seawater and shell carbonate. Several factors can be at play to cause this difference.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…We noted only a weak but significant positive correlation ( r 2 = 0.43-0.64, p-value < 0.001) for Mg/Mn, Cu/Mn, Zn/Mn and Sr/Mn, while Fe/Mn presented no significant correlation ( Supplementary Information 4 ). This difference in composition had already been observed and was probably due to vital effects (Weiner & Dove, 2003; Ulrich et al, 2021) induced by the metabolic filter between surrounding seawater and shell carbonate. Several factors can be at play to cause this difference.…”
Section: Resultsmentioning
confidence: 68%
“…Another reason for the difference in composition is that the shell is formed by a fluid derived from the external seawater in a compartment between the body and the calcifying carbonate, as the chemistry of this fluid is controlled by the larva (Ramesh et al, 2017). It has been demonstrated that organisms are able to change the pH of this fluid to increase calcification rate (Ramesh et al, 2017), which in turn favours Ca substitutions with other metals (Watson, 2004; DePaolo, 2011; Ulrich et al, 2021). Last but not least, mineralogy is also responsible for the selection of some elements over others in the carbonate lattice because of their atomic radii and charges.…”
Section: Resultsmentioning
confidence: 99%
“…Marine calcification has also been associated with elevated seawater Sr/Ca ratios (Lebrato et al., 2020). Since net community calcification includes the precipitation of both aragonite with slightly higher Sr/Ca ratio than seawater and calcite with very low Sr/Ca (1.80–5.69 mmol/mol (Ulrich et al., 2021)), the net community calcification effect on seawater Sr/Ca ratio may be dominated by the calcite calcification influence raising the Sr/Ca of ambient seawater. To assess the net ecosystem calcification rate, total alkalinity (TA) is a good indicator because it changes with calcification and dissolution of CaCO 3 in coral reefs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nTA (TA normalized to a constant salinity of 35) in Kaneohe Bay is largely restored every night from dissolution. Since the dissolution component is believed to be largely associated with more soluble forms of CaCO 3 such as high‐Mg calcite from coralline algae (Sr/Ca ratio 3.23 mmol/mol (Ulrich et al., 2021)) in the sediments (Shamberger et al., 2011), the net community effect on seawater Sr/Ca ratio in Kaneohe Bay remains uncertain in the absence of direct measurements. Furthermore, pCO 2 in Kaneohe Bay is known to be higher than open ocean waters entering from outside the bay (Shamberger et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At low salinity, organisms have higher physiological costs related to osmotic stress (Maar et al, 2015;Tedertgren & Kautsky, 1986), so it is easier for them to build calcite. However, the effect of salinity on skeletal polymorphism is complicated, as there are many aragonite species that exist in low salinity (e.g., Piwoni-Piórewicz et al, 2021) or even in freshwater environments (Dauphin et al, 2018), possibly owing to the evolution pathway of biomineralization mechanisms (e.g., Ulrich et al, 2021).…”
Section: Ions (Hco 3 −mentioning
confidence: 99%